Tramvajus ar metropolitenas Vilniaus urbanistinėje struktūroje. Vystymo prielaidos - Juškevičius, Pranciškus; Valeika, Vidualdas; Jauneikaitė, Kristina (Journal of Architecture and Urbanism, 2008)
Tram or metro in urban structure of Vilnius: development preconditions Until now and further in future the transportation problems of Vilnius will be caused by the mobility of inhabitants and their chosen communication means as well as the way of living in an urban structure or other type of environment. Regulation (management) of such a complex of factors is just a key to solving the problems. In today’s discussions no mention is made of the functional environment of tram or metro. Efforts to find proper development proportions for public and personal transportation systems are one of measures for a real problem solution. With this purpose in view actual social, political and financial environment as precondition for proper development of a transportation system, is indentified in the paper. Suggestions and arguments for implementing a tram system in Vilnius are given. Article in Lithuanian. Santrauka. Vilniaus susisiekimo problemas kūrė ir toliau kurs gyventojų mobilumas ir pasirenkamos susisiekimo priemonės, gyvenimo būdas urbanistinės struktūros ir kitokio tipo aplinkoje. Tokios visumos reguliavimas (valdymas) ir yra problemų sprendimo raktas. Dabartinėse diskusijose apie tokią visumą kaip apie tramvajaus, metropoliteno funkcionavimo aplinką neužsimenama. Šio straipsnio tikslas – identifikuoti susiklosčiusią socialinę, politinę ir finansinę aplinką kaip prielaidų lygį kokybiškai susisiekimo sistemai vystyti. Reikšminiai žodžiai: susisiekimo sistemos kokybė, komfortas, investicijų dydis, išorės kaina, tramvajus, metropolitenas, mobilumo struktūra. First Published Online: 22 May 2013